The prevalence and outcomes of α- and β-thalassemia among pregnant women in Hubei Province, Central China: An observational study. Issue 9 (4th March 2022) - Cheng, Yao; Chen, Miaomiao; Ye, Jiazhi; Yang, Qin; Wang, Ronggui; Liu, Shulian; Su, Rui; Song, Jieping; Gao, Tangxinzi; Xu, Runhong; Zhao, Feixia; Zhang, Peili; et al.
Abstract : Abstract: There is no information concerning the prevalence of thalassemia among pregnant women in Hubei Province currently. This study is aimed to explore the prevalence of α- and β-thalassemia genotypes among pregnant women in Hubei Province, and to explore the clinically applicable screening approach, as well as to investigate the pregnancy outcomes of α- and β-thalassemia carriers. Pregnant participants were recruited from 4 hospitals for the screening of α- and β-thalassemia mutations in Hubei Province. Polymerase Chain Reaction and flow cytometry methods were used to examine α- and β-thalassemia mutations. The hematological parameters and pregnancy outcomes of α- and β-thalassemia carriers were obtained from the hospital information system. The chi-square tests were used to evaluate the difference in hematological parameters between pregnant thalassemia carriers and the control group. Among 11, 875 participants, 414 (3.49%) were confirmed with α-thalassemia carriers, 228 (1.92%) were confirmed with β-thalassemia carriers, and 3 (0.03%) were confirmed with both α- and β-thalassemia carriers. The frequency of –α 3.7 accounted for 2.05% and it was the most frequent genotype of α-thalassemia; the proportion of IVS-II-654 was 0.85% and it was the most frequent genotype of β-thalassemia in Hubei Province. Furthermore, the proportion of patients with low mean corpuscular volume (MCV) or mean cell hemoglobin (MCH) values was accounted for 36.64% and 93.97% among α-thalassemia and β-thalassemia carriers, respectively. And participants with normal MCV and MCH values were accounted for 95.07% among non-thalassemia participants. High prevalence of pregnancy-induced diabetes (16.97%), preterm birth (9.96%), pregnancy-induced hypertension (8.12%), and low birth weight (5.90%) were observed among pregnant thalassemia carriers. MCV and MCH values were suggested to apply on the preliminary screening of pregnant β-thalassemia; however, it's unpractical on that of α-thalassemia. Furthermore, thalassemia carriers might have a high risk of negative pregnancy outcomes. These findings could be useful for the preliminary screening of thalassemia and perinatal care for the pregnant thalassemia carriers.